Audit Expectation Gap Debates: To What Extent Audit Expectation Gap Defence Auditors? - Adelia Yulma Budiarto (Bina Nusantara University, 2022)
The research aimed to unpack the debate of the audit expectation gap that occurs between the audit profession and the general public. This qualitative research intended to revisit what shapes audit objectives and their difficulties by drawing upon prominent academic debates and publicly available reports. This research argues that the concept of the audit expectation gap is two-fold. At first, the gap has been seen as destruction for the audit profession. However, to a certain extent, the gap is useful for auditors' defence mechanisms from critics, though auditors have to be alert that the gap might turn into an offensive medium and fuel the criticism. To illustrate this contention, this research argues the following. Firstly, the series of accounting scandals, changes of auditing standards towards fraud, and the phenomenon of audit explosion are giving more autonomy for auditors to protect the professions' best interest. Secondly, the issue of audit independence and conflict of interest is favourable for auditors to sustain the gap and maintain the monopoly of the audit business. Instead of being left behind, auditors earned public legitimacy because they manage to build a distinctive image as an expert who was able to work for the greater public interest in a complex, uncertain, conflicted, and stressful working environment. Thirdly, public demand for transparency is hurting audit professions because it increases public mistrust and might reveal audit confidentiality. It even fuels criticism further because auditors have communication difficulties.